Modern informational civilization and the problem of cultural self-determination - Zuyev, Andriy (Actual Problems of Mind, 2017)
The paper claims the necessity of transformation of theoretical approaches to the analysis of the problem of a person’s cultural self-determination. The author formulates a model for understanding the culture in information society based on a possibility of a choice between infinitely many symbolic-informational identification environments.